(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This article explores the significance of metaphor in language learning and translation. Metaphor, derived from the Greek word "to move," plays a crucial role in conveying meaning through language. The use of metaphorical expressions enables individuals to communicate concisely, vividly, and express the ineffable. Various scholars have examined metaphors in depth, highlighting their ability to shape worldviews and convey complex concepts. The challenges of translating metaphors across languages are also discussed, emphasizing the cultural and cognitive differences that can impact the effectiveness of literal translations. The article delves into different types of metaphors, including linguistic and artistic metaphors, and categorizes them based on their functions and effects. Overall, the study underscores the importance of understanding and interpreting metaphors in language learning and translation processes.